2019
DOI: 10.1111/tpj.14531
|View full text |Cite
|
Sign up to set email alerts
|

CG hypomethylation leads to complex changes in DNA methylation and transpositional burst of diverse transposable elements in callus cultures of rice

Abstract: SummaryCG methylation (mCG) is essential for preserving genome stability in mammals, but this link remains obscure in plants. OsMET1‐2, a major rice DNA methyltransferase, plays critical roles in maintaining mCG in rice. Null mutation of OsMET1‐2 causes massive CG hypomethylation, rendering the mutant suitable to address the role of mCG in maintaining genome integrity in plants. Here, we analyzed mCG dynamics and genome stability in tissue cultures of OsMET1‐2 homozygous (−/−) and heterozygous (+/−) mutants, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 79 publications
0
16
0
Order By: Relevance
“…In this study, 24 nt small RNA was shown to be positively correlated with DNA methylation. In rice, CG hypermethylation was seen in one-and three-year callus relative to the shoot in the mutant of rice MET1-2 that is a major DNA methyltransferase in maintaining CG methylation, but in the wildtype, only CHH hypermethylation was observed 45 . In our study, the callus versus seedling comparison showed that A188 MET1-2 homolog Zm00056a035610 was ~2x up-regulated in the callus, and mop1 (Zm00056a013519), a homolog of RNA-dependent RNA polymerase 2 that involved in the production of 24 nt small RNA 49 , was 5-6x up-regulated in the callus, indicating that the transcriptomic machinery was regulated to enhance globe DNA methylation in the callus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, 24 nt small RNA was shown to be positively correlated with DNA methylation. In rice, CG hypermethylation was seen in one-and three-year callus relative to the shoot in the mutant of rice MET1-2 that is a major DNA methyltransferase in maintaining CG methylation, but in the wildtype, only CHH hypermethylation was observed 45 . In our study, the callus versus seedling comparison showed that A188 MET1-2 homolog Zm00056a035610 was ~2x up-regulated in the callus, and mop1 (Zm00056a013519), a homolog of RNA-dependent RNA polymerase 2 that involved in the production of 24 nt small RNA 49 , was 5-6x up-regulated in the callus, indicating that the transcriptomic machinery was regulated to enhance globe DNA methylation in the callus.…”
Section: Discussionmentioning
confidence: 99%
“…Plant tissue culture from a highly differentiated tissue to the callus is the process of dedifferentiation to gain pluripotency for at least some cells 44 . For cells under tissue culture, the transition of differentiation status is a highly stressful procedure 45 . Our transcriptomic data revealed that defense genes were enriched among the callus featured genes that were up-regulated in the callus as compared to any other tissues examined.…”
Section: Discussionmentioning
confidence: 99%
“…Development from a highly differentiated tissue to the callus for genetic engineering purposes involves a process of dedifferentiation to gain pluripotency [ 51 ]. The transition of differentiation status is, physiologically, stressful [ 52 ]. Somaclonal variation, including sterility, in plants produced through tissue culture may be the product of DNA damaging stress responses [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In rice, CG hypermethylation was seen in 1- and 3-year callus relative to the shoot in the rice mutant MET1-2 , which encodes a DNA methyltransferase with a major role in maintaining CG methylation. In wildtype rice, however, only CHH hypermethylation was observed [ 52 ]. In our study, the callus versus seedling comparison showed that the A188 MET1-2 homolog (Zm00056a035610) was ~2× up-regulated in the callus, and mop1 (Zm00056a013519), a homolog of RNA-dependent RNA polymerase 2 that is involved in the production of 24 nt small RNA [ 56 ], was 5–6× up-regulated in the callus, indicating that the transcriptomic machinery was regulated to enhance global DNA methylation in the callus.…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance methylation occurs during DNA replication on hemimethylated CG and CHG contexts. De novo methylation occurs at all three unmethylated cytosines [3,9].…”
Section: Introductionmentioning
confidence: 99%